OSTEOPOROSIS TREATMENT WITH BISPHOSPHONATE THERAPY: A CLINICAL AUDIT - Sun, Jia Miin; Shahrizal, Shudim Saiful; See, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Osteoporosis is a progressive and debilitating bone disease with compromised bone strength leading to fragility fractures. Bisphosphonate is the predominant treatment for osteoporosis with an overall positive risk-benefit ratio. Pre-treatment counselling and standardized practice in prescribing bisphosphonate is important to ensure safety during treatment. METHODOLOGY This clinical audit was conducted to assess the practice of bisphosphonate prescription and pre-treatment counselling and assessment. All patients with osteoporosis and on active bisphosphonate treatment in Hospital Sultan Haji Ahmad, Temerloh, Central Pahang from August 2023 to January 2024 were included in the audit. Electronic medical records were assessed for demographic data, pre-treatment screening, DEXA scan investigations, pre-treatment counselling documentation, dental screening and secondary osteoporosis screening. RESULTS A total of 130 patients (86% females) were on active bisphosphonate treatment. Of these, 48 (36.9%) patients were from 70-79 years of age. Majority of the treatment was initiated by orthopaedic surgeons (63.8%) and endocrinologists (15.4%). Fragility fracture was the most common indication for bisphosphonate therapy in 56.9%. The most prevalent risk factors for osteoporosis were postmenopausal (80.7%), followed by prolonged steroid use (18.5%) and other endocrine disorders (11.5%). Only 35.3% (n=48) had bone mineral densitometry done prior to initiation of treatment. Less than 10% of patients had documented fracture risk assessment with FRAX. About 40% of patients had no baseline renal function prior to initiation of treatment. Referral for dental screening was not documented in 48.5% of patients. There was also a lack of counselling and documentation prior to the initiation of treatment. Majority of patients (86.9%) received vitamin D and calcium supplementation with bisphosphonate therapy. CONCLUSION A standardized osteoporosis pre-treatment checklist is required to ensure good and safe practice of treatment. Awareness and appropriate counselling among patients with osteoporosis on bisphosphonate treatment needs to be improved.